A Comprehensive Study of Capacitive Loaded Resonant Converter Topologies for Charging Applications - Geethanjali Pandeswara; Naresh Pasula (IAES Indonesian Section, 2021)
Resonant converters (RCs) are perceiving global interests of the research community for its eminent contribution in design of many industrial and commercial applications. Rich literature and well-established technology is available to define the role of RCs in such applications where the load is predominantly passive and resistive. However in applications like charging, the nature of load is often interpreted as capacitive and the knowledge on how a RC reciprocates to such variable, non linear load is limited. Motivated by this, the paper investigates about 25 capacitive loaded resonant structures and each of them is thoroughly analyzed to evaluate various key parameters like the output current, peak input current, and current gain. A comparative study is done to categorize and organize these topologies in regard to each of the said parameters. This provides a quick overview of various resonant converter topologies and helps designers to choose a structure that may fit their application. To this base knowledge, the study is further narrowed down to find suitable topology for charging application and accordingly proposed a novel fourth-order RC topology called LA7. A hardware prototype was built to compare and validate the simulated and measured performances.